A PLK1 inhibitor, RO3280, suppresses proliferation of SNU-16 gastric cancer cells via apoptosis - Fatih Yulak; Zekeriya Keskin (Bangladesh Pharmacological Society, 2024)
This study examines the anti-tumor, pro-apoptotic, and genotoxic effects of polo-like kinase 1 (PLK1) inhibitor RO3280 on the gastric cancer cell line SNU-16. Using the XTT assay, the antiproliferative effect of the compound was identified and showed a significant antiproliferative effect (p<0.01) with the IC50 value of 9.64 µM for 24 hours. RO3280 considerably enhanced the expression of Bax and cleaved caspase-3 (p<0.01) and dramatically lowered the BCL-2 level (p<0.01), demonstrating an apoptotic effect. It greatly raised the expression of 8-oxo-dG, a DNA damage marker, and cleaved PARP, a degraded version of the PARP enzyme involved in DNA repair (p<0.05 and p<0.01, respectively). In addition, flow cytometric studies for annexin V and caspase-3/7 revealed that RO3280 markedly improved the apoptotic cell profile (p<0.01). It reduced the mitochondrial membrane potential and DNA damage (p<0.01). These findings suggest that RO3280 has an antitumor impact by damaging DNA and inducing apoptosis in SNU-16 gastric cancer cells.